2023
DOI: 10.3390/app13042040
|View full text |Cite
|
Sign up to set email alerts
|

Series PIDA Controller Design for IPDT Processes

Abstract: This paper discusses optimal design of the series proportional–integral–derivative–accelerative (PIDA) controller for integral-plus-dead-time (IPDT) plants. The article starts with the design of disturbance reconstruction and compensation based on proportional-derivative-accelerative (PDA) stabilizing controllers. It shows that by introducing positive feedback by a low-pass filter from the (limited) output of the stabilizing PDA controller, one gets disturbance observer (DOB) for the reconstruction and compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Several recent works have shown that it is possible to design higher order constrained controllers. These structures combine stabilizing controllers (using higher-order derivatives) with automatic reset, guaranteeing disturbance reconstruction and compensation of disturbances [26,27,35]. Automatic-reset and hyper-reset (pre-act)-based controllers were invented before the World War II, although they have largely disappeared from the literature due to the dominance of linear control theory.…”
Section: Parallel Pida and Pida Controllers With Automatic Resetmentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent works have shown that it is possible to design higher order constrained controllers. These structures combine stabilizing controllers (using higher-order derivatives) with automatic reset, guaranteeing disturbance reconstruction and compensation of disturbances [26,27,35]. Automatic-reset and hyper-reset (pre-act)-based controllers were invented before the World War II, although they have largely disappeared from the literature due to the dominance of linear control theory.…”
Section: Parallel Pida and Pida Controllers With Automatic Resetmentioning
confidence: 99%
“…Due to the interpretations by linear control theory, even the series controllers are not well understood in practice. As a result, users are not aware of the role of disturbance observers in automatic reset controllers, although it is important for optimal controller tuning and constrained system control (see also [26,27,35,39]). Recently, clarification of some key conceptual differences between series and parallel controllers with higher-order derivatives has enabled substantial progress in the design of constrained controllers for the simplest processes that can be adequately approximated by the first-order models with dead time.…”
Section: Parallel Pida and Pida Controllers With Automatic Resetmentioning
confidence: 99%
See 3 more Smart Citations